Evaluasi Kebutuhan Pompa Multliflow MF-420EXHV Untuk Pengeringan Sump di Pit 7 West PT. Bukit Makmur Mandiri Utama Jobsite Binungan Suaran - Tiwi Melisa; Yoszi Mingsi Anaperta; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Mining activities carried out by PT. Bukit Makmur Mandiri Utama Jobsite Binungan Suaran uses a combination method of digging and loading (excavator) and transportation equipment (dump truck). The mining system implemented by PT. Bukit Makmur Mandiri Utama Jobsite Binungan Suaran is a surface mining system with the open pit method. The application of the open pit method will cause the formation of large basins so that it is very potential to become a water storage area, both from surface runoff and groundwater. At pit 7 west PT. Bukit Makmur Mandiri Utama Jobsite Binungan Suaran, there is a sump located at an elevation of -101 masl. Directly below the sump is a coal seam. Economically, the layer is feasible to be mined, so that the sump drying is planned, it is necessary to evaluate the pump capacity currently used so that the drying process can run well according to the target time so that the mining process can be carried out immediately. A dewatering system is used to dry the sump. Based on the results of the analysis that has been done, the catchment area in pit 7 WEST is 312.04 ha, with a planned rainfall of 8.46 mm / day and a rain intensity of 1.14 mm / hour. Water discharge Surface runoff by rainwater in the catchment area 7 west is 24769.04 m3 / day, groundwater discharge is 386.12 m3 / day and evapotranspiration discharge is 128.61 m3 / day. So that the total volume of water that enters the 7 west sump pit is 25026 m3 / day. So, the number of Multiflo MF- 420EXHV pumps needed to compensate for the daily discharge in the MTBU-B area is 2 pump units, with a pump working duration of 20 hours / day.Keywords: Open pit, Pit 7 west, Sump, Water Discharge, Pump